2022
DOI: 10.1016/j.padiff.2022.100282
|View full text |Cite
|
Sign up to set email alerts
|

Stability analysis and Hopf bifurcation in fractional order SEIRV epidemic model with a time delay in infected individuals

Abstract: Infectious diseases have been a constant cause of disaster in human population. Simultaneously, it provides motivation for math and biology professionals to research and analyze the systems that drive such illnesses in order to predict their long-term spread and management. During the spread of such diseases several kinds of delay come into play, owing to changes in their dynamics. Here, we have studied a fractional order dynamical system of susceptible, exposed, infected, recovered and vaccinated population w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…A Mahata et al [ 23 ], a fractional order dynamical system of susceptible, exposed, infected, recovered, and vaccinated populations was shown, with a single delay added in the infectious population to account for the time necessary for the said population to recover. They used the Adam–Bashforth–Moulton approach to derive numerical solutions to the model system.…”
Section: Related Workmentioning
confidence: 99%
“…A Mahata et al [ 23 ], a fractional order dynamical system of susceptible, exposed, infected, recovered, and vaccinated populations was shown, with a single delay added in the infectious population to account for the time necessary for the said population to recover. They used the Adam–Bashforth–Moulton approach to derive numerical solutions to the model system.…”
Section: Related Workmentioning
confidence: 99%
“…Many studies have been conducted in the field of mathematics, and it has been shown that differential equations using fractional operators are effective in demonstrating epidemic models linked to many infectious illnesses [7,12]. Two leading implementations of fractional calculus are in epidemiological and biomathematical models [6,18,19]. Ahmad et al [2] performed simulations of a fractional model for CoViD-19 transmission, taking into account various values of the non-integer order derivative and came to the conclusion that the value of = 0.97 best matched the actual data.…”
Section: Introductionmentioning
confidence: 99%
“…FDEs with deviated arguments have many applications in science and engineering, including fractals theory, chemistry, biology, physics, neural network, weather prediction model, etc. [19,26]. Brauer et al [5] presented logistic equations, which are particularly applicable to epidemic systems.…”
Section: Introductionmentioning
confidence: 99%
“…At present times an extensive investigation [10][11][12][13][14][15][16][17][18][19][20][21][22][23] of the spread of the highly contagious Coronavirus disease with alarming fatality rate is being carried out. Different models exist in epidemiology to forecast and explain the complexities of an epidemic.…”
Section: Introductionmentioning
confidence: 99%